Strategies for Developing Numeracy Literacy in Junior High Schools in Indonesia: a Literature Review - Nia Muniasari; Delia Elvaryssa Lovelly; Aan Anisah; Nasir Asman (LITERACY : International Scientific Journals of Social, Education, Humanities, 2024)
The ability in literacy and numeracy is crucial for students at the Junior High School (SMP) level. Teachers and parents play vital roles in developing the literacy and numeracy skills of students. Understanding students' reading and mathematical interests is also important for enhancing their literacy and numeracy abilities. The following study is conducted to analyze strategies for developing numeracy literacy among Junior High School students to enhance their skills. This study is referred to as a literature review. Methods for gathering information include reading, writing, tracking, and analyzing research data objectively, systematically, analytically, and critically related to literacy and numeracy development strategies. The aim of this review is to provide important details from several previous studies to assist researchers in obtaining comprehensive sources. These findings are expected to provide a proper understanding to learners regarding strategies for developing numeracy literacy to improve learners' literacy and numeracy skills.